Mucosite oral induzida por 5-fluorouracil em hamsters persiste após o bloqueio farmacológico da via dos leucotrienos - Silva, Viviane Carvalho (2017)
Oral mucositis (OM) is an important adverse effect in patients undergoing cancer treatment. Its pathophysiology is still not fully understood and causes discomfort and treatment interruptions, contributing to a worse prognosis. The relationship of the cyclooxygenase-2 (COX-2) pathway with the MO to chemotherapeutic agents is known, but the role of leukotrienes (another arachidonic acid metabolite and one of the actors in inflammatory processes of the gastrointestinal mucosa) is not determined. An experimental study of 5-fluorouracil induced OM in hamsters was conducted to investigate the participation of cysteinyl leukotrienes (cys-LT) in their pathophysiology. The study had two parts: 1st experiment: four control groups 1) 5-FU: animals submitted to oral mucositis; 2) SAL: animals not submitted to oral mucositis or normal control; 4) CLX (standard treatment group): animals with OM who received celecoxib (7.5 mg/kg/day, intraperitoneal) 1 hour before the administration of 5-fluorouracil, and daily until the tenth day) and three treatment groups: animals with OM and montelukast (MTK) cys-LT blockade (10 or 20 or 40 mg/kg/day/10 days; orally by gavage). The controls groups used were the same as those of the 1st experiment, except for the CLX group and the treatment group had blocked the leukotriene synthesis cascade by MK886 (inhibitor of 5-lipoxygenase synthesis) (3mg/kg/day; intraperitoneal) for 4 days, given 1 hour before 5-fluorouracil administrations and daily until the 4th experimental day. In both experiments the animals were euthanized on the 10th day and macroscopic analysis of the jugal mucosa was performed, as well as histopathological evaluation for hematoxylin-eosin, immunohistochemical evaluation for iNOS2, COX-2, IL1-β, TNF-α and IL10 for all experimental groups and dosage of myeloperoxidase for the animals of the 2nd experiment. Montelukast presented partial protection at a dose of 40mg/kg/day in the macroscopic evaluation, but in the other doses administered there was no protection. MK886 did not macroscopically protect the progression of OM by 5-fluorouracil. Myeloperoxidase activity was not reduced by the use of MK886 for four days. Montelukast or MK886 were unable to protect the animals from OM in the histopathological evaluation by hematoxylin-eosin, and unable to reduce the expression of iNOS2, COX-2 and IL1-β. But montelukast and MK886 decreased TNF-α expression at all doses used. Montelukast promotes a decrease in IL-10 expression at a dose of 40mg/kg/day. COX-2 blockade reduced the expression of iNOS2, COX-2, IL-1β and TNF-α, but was unable to induce decreased expression of IL10. Differing from the COX-2 pathway, the leukotriene pathway is not relevant in the pathophysiology of the 5-fluorouracil induced oral mucositis model. However, its effect on TNF-α suggests a modulating action specifically on this cytokine.